FLY ASH-GEOPOLYMER COMPOSITE OBTAINED BY ADDITION OF RECYCLED POST-CONSUMER PACKAGING BOTTLE - Lucian Paunescu; Eniko Volceanov; Marius Florin Dragoescu; Bogdan Valentin Paunescu (Nonconventional Technologies Review)
The experiment described in this paper is part of the series of worldwide investigation of the influence of different types of alumina-silicate waste on properties of geopolymer concrete. The work originality consists in the choice of recycled post-consumer green packaging bottle as a partial substitute for fly ash, unlike recent results known from the literature of the use of brown glass waste powder or in a mixture of coloured glass. The results showed that the replacement of 18 % of the initial fly ash content is an optimal solution to increase the compression and flexural strength of the geopolymer concrete both after 7 days of storage and after 28 days. In this case, the compression resistance values ​​reached 34.8 and 46.0 MPa, respectively and the flexural resistance values ​​were 5.9 and 8.9 MPa, respectively. Further increasing the proportion of green glass up to 30 % contributed to a surplus of concrete strength, but to a very small extent, reaching a maximum of 34.9 and 47.0 MPa and respectively, 6.0 and 9.1 MPa.